2008
DOI: 10.1111/j.1574-0862.2008.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying cointegration and error correction to measure trade linkages: maize prices in the United States and Mexico

Abstract: The impact of U.S.-grown maize on Mexican markets is a subject of heated debate, and is complicated by limited substitution between white and yellow maize as well as regional price differences within Mexico. This article improves on previous analyses using a detailed data set of white maize prices reported weekly in 11 states across Mexico from 1998 through 2005. Using cointegration analysis and the error-correction model, we find that prices between the United States and Mexico do not share a common long-run … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The long-run causality between price variables is investigated by applying Wald test for the coefficients of α, which are referred to as weak exogeneity tests. This causality is typically interpreted as price leadership (Motamed, Foster, and Tyner, 2008).…”
Section: Weak Exogeneity Testmentioning
confidence: 99%
“…The long-run causality between price variables is investigated by applying Wald test for the coefficients of α, which are referred to as weak exogeneity tests. This causality is typically interpreted as price leadership (Motamed, Foster, and Tyner, 2008).…”
Section: Weak Exogeneity Testmentioning
confidence: 99%
“…For this reason, tomato prices in the producer and consumer markets do not drift apart in the long run (Motamed, Foster and Tyner, 2008). In this case, price changes resulting from random market shocks on any producer market will be expected to reflect as changes in the prices of the commodity in all other markets, assuming unchanged transaction costs.…”
Section: Source: Authors' Own Estimations From Datasetmentioning
confidence: 99%
“…Generally, economists consider price‐based market integration tests to be more definitive and reliable than the quantity‐based ones (Ghemawat, 2001; Vinuya, 2007). The primary method used for studying market integration is cointegration analysis (e.g., Alexander and Wyeth, 1994; Baffes, 1991; Motamed et al, 2008; Warell, 2006). A great number of such studies have shown a long‐run linkage among prices of selected agricultural commodities (e.g., Booth and Ciner, 2001; Liu, 2005; Malliaris and Urrutia, 1996).…”
Section: Introductionmentioning
confidence: 99%